Online Internal Quality Assurance System Case Study of the Quality Assurance Agency of Muhammadiyah University of Sidoarjo - Febrian Endi Pranyoto; Rohman Dijaya (Universitas Muhammadiyah Sidoarjo, 2022)
Internal Quality Assurance System (SPMI) is a system used to control the quality of education implementation. The quality of education is used as the front line in the formation of competent Human Resources (HR), because if the quality of education is low, it will have an impact on the lack of Human Resources. The implementation of SPMI at Muhammadiyah University of Sidoarjo is carried out by the Quality Assurance Agency (BPM). BPM has an obligation to regulate the SPMI cycle from designing, compiling, and setting quality standards for universities. The BPM process for collecting data used for quality assurance is still quite manual and takes a long time. The system was developed to assist the website-based quality assurance process. Researchers use the data in BPM as material to create a website that is used to assist the guarantee process which will then be grouped into each study program and faculty. By using the help of the PHP programming language and MySQL database, and Internal Online Quality Assurance System was obtained. With this system, it is evident that the development of an Internal Online Quality Assurance System is very helpful in the quality assurance process in BPM.